Knowledge of Body Weight, Body Image and Gestational Weight Gain Among Pregnant Women. - Ritmontree , Orawan; Xuto , Piyanut; Sriarporn , Punpilai (Nursing Journal CMU, 2020)
Gestational weight gain affects maternal health and fetal outcomes. The purpose of this descriptive correlational research was to examine whether there was a relationship between knowledge of body weight, body image, and gestational weight gain among pregnant women. The study sample consisted of one hundred and ninety-four participants, all of whom were pregnant women who had normal pre-pregnancy body mass index, and had gestational age of 36 weeks and selected by purposive sampling. The participants were taken from the antenatal clinics at Maharaj Nakhonsithammarat Hospital from September to November 2013. The research instruments used were Knowledge of Weight Gain Evaluation questionnaire, developed by Ritmontree, Xuto, & Sriarporn, based on the literature reviewed; and the Body Image Rating Scale, developed by Souto & Garcia (2002) which was translated and adapted into the Thai language by Sirirat Sarit-apirak (Sarit-apirak, 2008). Descriptive statistics and the Spearman rank order correlation coefficient were used to analyze the data. Results of the study revealed that: The mean score of knowledge of body weight was 20.24 (S.D.= 4.83). There was 81.44% of participants having good knowledge of weight gain. The mean score of body image was 87.35 (S.D. = 12.88). There was 56.19% of participants having moderate perception of body image. The mean score of gestational weigh gain was 12.76 kilogram (S.D.=4.50) . There was a significant moderate negative correlation between Knowledge of weight gain and gestational weight gain among pregnant women (r = -.315, p < .01). 3. There was a significant low negative correlation between body image and gestational weight gain among pregnant women (r = -.143, p < .05). These findings could be used to enhance knowledge of weight gain, body image, and gestational weight gain among pregnant women, and to advise pregnant women on appropriate weight gain.